Why critical psychology and the neurodiversity movement need each other - Thomas, Eleanor (Frontiers in Psychology, 2024)
Critical psychology is a discipline that can be defined in a variety of ways, though common themes include critiquing mainstream psychology as well as critiquing society at large and engaging in social change to respond to those critiques. The neurodiversity movement is a political movement that emerged in response to the dehumanizing treatment of Autistic and other neurodivergent individuals by society in general and by mainstream psychology specifically. In this article, I describe five ways in which critical psychology and the neurodiversity movement can and have begun to benefit from each other: (a) by critical psychologists embracing neurodivergent epistemologies in the way they embrace other diverse epistemologies; (b) by resisting attempts within mainstream psychology to pathologize difference or “treat” these so-called psychopathologies by modifying behavior; (c) by practitioners developing cultural competency around neurodivergent culture within the psychotherapeutic practice; (d) by challenging the homogenization and whitewashing within the neurodiversity movement through leveraging lessons from within various critical psychologies; and (e) by researchers and practitioners recognizing and combatting instances of ableism embedded in other forms of oppression and within the field of critical psychology itself.